Monkeypox – An update - Rahman Mamun, Mohammad Mominur; Pasha, AKM Mustafa Kamal (Journal of Armed Forces Medical College, Bangladesh, 2022)
Abstract not available JAFMC Bangladesh. Vol 18, No 1 (June) 2022: 1-2